Drug-Induced Lung Injury (Respiratory Disease Series: Diagnostic Tools and Disease Managements,, 2018)
This book covers various aspects of a respiratory system disorder associated with prescribed drugs that do not yet have established treatment guidelines, and for which the only treatment is to discontinue taking the drug. Very little clinical evidence regarding the disorder is available, since randomized trials cannot to be carried out, the onset of the disorder cannot be predicted, and the resulting pathological condition is life-threatening. However, the need for an established treatment continues to grow due to the introduction of many new drugs, such as anti-neoplastic drugs, biological products, and molecular target drugs, the adverse effects of which are difficult to differentiate from those of other lung diseases, such as lung infectious diseases. Drug-Induced Lung Injury offers a highly beneficial resource not only for respiratory physicians but also all medical clinicians who prescribe drugs, nurses, pharmacists and pharmaceutical scientists. Written by pioneering experts in the field, the book examines a wealth of cases and the insights they yield concerning the diagnosis, treatment and specific drugs causing the disease. It not only fosters a deeper understanding of the disorder but also highlights the current challenges and paves the way for future clinical research.